2021
DOI: 10.1002/asl.1034
|View full text |Cite
|
Sign up to set email alerts
|

Modification of raindrop size distribution due to seeder–feeder interactions between stratiform precipitation and shallow convection observed by X‐band polarimetric radar and optical disdrometer

Abstract: The seeder-feeder interactions (SFIs), where raindrops from upper clouds grow by accreting cloud droplets in the lower clouds, have been extensively studied. However, there are few studies on the modification of raindrop size distribution (DSD) through this process. In the present study, rainfall from the landfalling rainbands of a typhoon was observed using an optical disdrometer and an X-band polarimetric radar. Rainfall was classified into the following three types based on the DSD characteristics at the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…기후변화 영향으로 국내의 강우 현상이 불규칙적으로 변하 고 있다. 최근 5년 변화를 살펴보면 2016년과 2017년에는 강우 부족으로 지역적인 가뭄이 심각하게 나타났으나, 이후 강우량이 점차 증가하여 2020년에는 수도권에 기록적인 폭우 현상이 발생하였다 (KMA, 2016;2017;2020a) (Matrosov, 2021;Misumi et al, 2021;Reinoso-Rondinel and Schleiss, 2021;Shin et al, 2021;Thurai et al, 2021;Wang et al, 2021) (Meischner, 2005). 비차등위상은 주어진 거리에서 수평파와 수직파의 위상차 를 나타낸는 것으로 차폐, 지형, 이상전파의 영향을 적게 받기 때문에 반사도와 함께 강수 분석에 이용된다 (Kumjian, 2013).…”
Section: 서 론unclassified
“…기후변화 영향으로 국내의 강우 현상이 불규칙적으로 변하 고 있다. 최근 5년 변화를 살펴보면 2016년과 2017년에는 강우 부족으로 지역적인 가뭄이 심각하게 나타났으나, 이후 강우량이 점차 증가하여 2020년에는 수도권에 기록적인 폭우 현상이 발생하였다 (KMA, 2016;2017;2020a) (Matrosov, 2021;Misumi et al, 2021;Reinoso-Rondinel and Schleiss, 2021;Shin et al, 2021;Thurai et al, 2021;Wang et al, 2021) (Meischner, 2005). 비차등위상은 주어진 거리에서 수평파와 수직파의 위상차 를 나타낸는 것으로 차폐, 지형, 이상전파의 영향을 적게 받기 때문에 반사도와 함께 강수 분석에 이용된다 (Kumjian, 2013).…”
Section: 서 론unclassified
“…These are exacerbated by blockage by local obstructions or complex terrain. Dense networks of limited range small radars to sense the lowest levels of the atmosphere have been proposed (Mclaughlin et al 2009) and have been deployed for demonstration in several urban environments (Cifelli et al 2018;Misumi et al 2020;Chandrasekar et al 2018).…”
Section: Clouds and Precipitationmentioning
confidence: 99%
“…A well‐known phenomenon of mixed precipitation features is the seeder–feeder effect (e.g., Misumi et al, 2021; Rutledge & Hobbs, 1983). Misumi et al (2021) demonstrated the vertical process of the seeder–feeder effect in convective clouds with a melting layer by analyzing typhoon observations.…”
Section: Introductionmentioning
confidence: 99%
“…A well‐known phenomenon of mixed precipitation features is the seeder–feeder effect (e.g., Misumi et al, 2021; Rutledge & Hobbs, 1983). Misumi et al (2021) demonstrated the vertical process of the seeder–feeder effect in convective clouds with a melting layer by analyzing typhoon observations. Ahmad et al (2020) showed that a couple of precipitation cells merged to form a system of multiple cells having various precipitation features.…”
Section: Introductionmentioning
confidence: 99%